3F.003 Safety data sheets exposed; the implications of poor and inaccurate SDS - Stevens, Lisa (Abstracts, 2021)
Safety data sheets contain critical information for the safe use, handling, storage, transportation and disposal of chemicals. SDS’s provide essential information for the production of risk assessments. The reliance of such documents by occupational health and safety professionals, chemists, and students is massive.As health and safety professionals it is important to understand that all safety data sheets are not necessarily equal. But how do you know if the information contained on the SDS is accurate? What are the implications/ramifications of having an inaccurate data and information of the SDS?This is paper is a case study surrounding the purchase of a pack of irritant smoke tubes used for the testing of fume cupboards, and the ongoing narrative which occurred when an importing supplier was asked for an Australian GHS Compliant safety data sheet.This presentation also looks at the implications of a poorly written SDS and the possible consequences of an inaccurate information, as well as raising questions about the use of third party SDS and who can be considered as a ‘subject matter expert’.